10 tháng 7 lúc 8:50

Bài 2:

$\left(x-1\right)^3=\dfrac{1}{8}\\ \Leftrightarrow\left(x-1\right)^3=\left(\dfrac{1}{2}\right)^3\\ \Rightarrow x-1=\dfrac{1}{2}\\ \Leftrightarrow x=\dfrac{3}{2}\\ \left(3-x\right)^3=-\dfrac{27}{64}\\ \Leftrightarrow\left(3-x\right)^3=\left(-\dfrac{3}{4}\right)^3\\ \Leftrightarrow3-x=-\dfrac{3}{4}\\ \Rightarrow x=\dfrac{15}{4}\\ \left(x-5\right)^3=\dfrac{1}{-27}\\ \Leftrightarrow\left(x-5\right)^3=\left(\dfrac{1}{-3}\right)^3\\ \Rightarrow x-5=-\dfrac{1}{3}\\ \Leftrightarrow x=\dfrac{14}{3}\\ \left(x-4\right)^2=\dfrac{4}{9}\Leftrightarrow\left(x-4\right)^2=\left(\dfrac{2}{3}\right)^2\\ \Leftrightarrow x-4=\dfrac{2}{3}\\ \Rightarrow x=\dfrac{14}{3}\\ \left(5-x\right)^2=\dfrac{1}{16}\\ \Leftrightarrow\left(5-x\right)^2=\left(\dfrac{1}{4}\right)^2\\ \Leftrightarrow5-x=\dfrac{1}{4}\\ \Rightarrow x=\dfrac{19}{4}\\ \left(x+1\right)^2=\dfrac{4}{49}\\ \Leftrightarrow\left(x+1\right)^2=\left(\dfrac{2}{7}\right)^2\\ \Leftrightarrow x+1=\dfrac{2}{7}\\ \Leftrightarrow x=-\dfrac{5}{7}$

Bình luận (0)
10 tháng 7 lúc 19:24

Bài 3:

$1.\left(x-\dfrac{1}{2}\right)^3=\left(-2\right)^3\\ \Leftrightarrow x-\dfrac{1}{2}=-2\\ \Leftrightarrow x=-\dfrac{3}{2}\\ 2.\left(x-\dfrac{1}{2}\right)^3=\left(\dfrac{3}{2}\right)^3\\ \Leftrightarrow x-\dfrac{1}{2}=\dfrac{3}{2}\\ \Leftrightarrow x=2\\ 3.\left(x-\dfrac{1}{3}\right)^3=\left(-\dfrac{2}{3}\right)^3\\ \Leftrightarrow x-\dfrac{1}{3}=-\dfrac{2}{3}\\ \Leftrightarrow x=-\dfrac{1}{3}\\ 4.\left(x-\dfrac{1}{3}\right)^3=\left(\dfrac{2}{3}\right)^3\\ \Leftrightarrow x-\dfrac{1}{3}=\dfrac{2}{3}\\ \Leftrightarrow x=1\\ 5.\left(x-\dfrac{5}{2}\right)^3=\left(-\dfrac{1}{2}\right)^3\\ \Leftrightarrow x-\dfrac{5}{2}=-\dfrac{1}{2}\\ \Leftrightarrow x=2\\ 6.\left(x-\dfrac{1}{8}\right)^3=\left(-\dfrac{2}{5}\right)^3\\ \Leftrightarrow x-\dfrac{1}{8}=-\dfrac{2}{5}\\ \Leftrightarrow x=-\dfrac{11}{40}\\ 7.\left(x+\dfrac{1}{2}\right)^2=\left(\dfrac{1}{4}\right)^2\\ \Leftrightarrow x+\dfrac{1}{2}=\dfrac{1}{4}\\ \Leftrightarrow x=-\dfrac{1}{4}\\ 8.\left(x-\dfrac{3}{2}\right)^2=\left(\dfrac{3}{4}\right)^2$

$\Leftrightarrow x-\dfrac{3}{2}=\dfrac{3}{4}\\ \Leftrightarrow x=\dfrac{9}{4}\\ 9.\left(x-\dfrac{5}{6}\right)^2=\left(\dfrac{1}{6}\right)^2\\ \Leftrightarrow x-\dfrac{5}{6}=\dfrac{1}{6}\\ \Leftrightarrow x=1\\ 10.\left(x+\dfrac{2}{5}\right)^2=\left(\dfrac{3}{4}\right)^2\\ \Leftrightarrow x+\dfrac{2}{5}=\dfrac{3}{4}\\ \Leftrightarrow x=\dfrac{7}{20}\\ 11.\left(x+\dfrac{1}{12}\right)^2=\left(\dfrac{4}{3}\right)^2\\ \Leftrightarrow x+\dfrac{1}{12}=\dfrac{4}{3}\\ \Leftrightarrow x=\dfrac{5}{4}\\ 12.\left(x-\dfrac{4}{7}\right)^2=\left(\dfrac{1}{7}\right)^2\\ \Leftrightarrow x-\dfrac{4}{7}=\dfrac{1}{7}\\ \Leftrightarrow x=\dfrac{5}{7}$

Bình luận (0)
9 tháng 7 lúc 23:04

Đề dài quá. Bạn nên tách nhỏ từng bài một để đăng nhé. Mọi người sẽ dễ theo dõi và hỗ trợ hơn.

Bình luận (1)

Các câu hỏi tương tự
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết